Pembuktian Unsur Berencana dalam Tindak Pidana Pembunuhan Berdasarkan Perspektif Kriminologi - Fransiska Devi Silvana (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Premeditated murder is a severe crime characterized by prior planning (voorbedachte raad), making the proof of premeditation crucial in criminal justice. This element is linked to the mental state of the perpetrator, which cannot be directly proven but must be inferred from objective facts and events. Legal proof often focuses on the elements of Article 340 of the Criminal Code, overlooking criminological aspects such as motives, background, and the process of intent formation. This study analyzes how premeditation is proven in murder cases from a criminological perspective and evaluates the relevance of criminological approaches in judicial deliberations. Using a normative legal method with statutory, conceptual, and case approaches, supported by philosophical, sociological, and criminological studies, the research finds that proving premeditation requires more than legal indicators like time delay, tool preparation, and structured actions. It also involves understanding the perpetrator's psychological, social, and situational factors. A criminological perspective helps explain the formation of criminal intent, offering a more comprehensive view of premeditation. Integrating criminology into judicial decisions can enhance evidence quality, leading to more substantive and just outcomes.